1999
DOI: 10.1007/s004300050098
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystis carinii infection in young non-immunosuppressed rabbits. Kinetics of infection and of the primary specific immune response

Abstract: The aim of this study was to determine the kinetics, the dissemination of the infection and the immunological response to Pneumocystis carinii primary infection in a non-immunosuppressed rabbit model. For this purpose, we developed a nested PCR that amplified a portion of the mitochondrial large-subunit rRNA gene of rabbit-derived P. carinii. The PCR detected P. carinii DNA in lung and bronchoalveolar lavage fluids from 14- to 45-day-old rabbits but not in their serum. No P. carinii DNA was detected in extrapu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…It seems unlikely that in nature, the number of immunodeficient hosts is adequate to perpetuate this organism. It has already been shown that immunocompetent infant animals can acquire Pneumocystis from infected mothers (3,7,15,23) and that the organisms persist for several weeks. In addition, recent work by others has shown that immunocompetent mice can transmit P. carinii f. sp.…”
Section: Vol 71 2003 Pneumocystis Infection In Cohoused Mice 2069mentioning
confidence: 99%
See 1 more Smart Citation
“…It seems unlikely that in nature, the number of immunodeficient hosts is adequate to perpetuate this organism. It has already been shown that immunocompetent infant animals can acquire Pneumocystis from infected mothers (3,7,15,23) and that the organisms persist for several weeks. In addition, recent work by others has shown that immunocompetent mice can transmit P. carinii f. sp.…”
Section: Vol 71 2003 Pneumocystis Infection In Cohoused Mice 2069mentioning
confidence: 99%
“…Recent studies suggest that children may frequently harbor Pneumocystis in their lungs (17,24,26), and animal experiments have shown that neonatal mice, pigs, and rabbits can harbor substantial numbers of Pneumocystis organisms (3,7,15,23). However, after intratracheal instillation of Pneumocystis carinii f. sp.…”
mentioning
confidence: 99%
“…Nonimmunosuppressed young rabbits routinely develop microscopically detectable infections with Pneumocystis early after birth that can reach burdens in the millions of organisms (26,28). The infection is gradually resolved as the immune system matures.…”
Section: Vol 1 2002 Early Acquisition Of P Carinii In Rats 417mentioning
confidence: 99%
“…The ability to detect P. carinii DNA in oral swab samples represents a significant technical breakthrough that can be used to increase our understanding of the life cycle of P. carinii in an antemortem setting. Sampling of the oral cavity and PCR detection of Pneumocystis have now been authenticated as a means to determine Pneumocystis exposure in two mammalian hosts, rats and humans, in both immunosuppressed and nonimmunosuppressed states (7,10,12,18,28,31). Besides the obvious diagnostic application, this technique provides an experimental tool that can be used for selection of rats exposed to P. carinii prior to induction into an experiment, so that investigators need not wait to discover the presence of the organism in control animals after 8 to 12 weeks of immunosuppression.…”
Section: Vol 1 2002 Early Acquisition Of P Carinii In Rats 417mentioning
confidence: 99%
“…Presently, evidence that primary PCP is caused by reinfection rather than reactivation is based on animal experiments, in which primary infection is completely cleared (27,32), and autopsy studies, in which P. carinii DNA is not detected in immunocompetent adults (25). However, whether reactivation or reinfection causes recurrent PCP in HIV-infected patients may be more complex.…”
mentioning
confidence: 99%